In Vivo and Ex Vivo Comprehensive Evaluation of Corneal Reinnervation in Eyes Neurotized With Contralateral Supratrochlear and Supraorbital Nerves. Issue 2 (February 2020) - Giannaccare, Giuseppe; Bolognesi, Federico; Biglioli, Federico; Marchetti, Claudio; Mariani, Silvia; Weiss, Jayne S.; Allevi, Fabiana; Cazzola, Federica E.; Ponzin, Diego; Lozza, Alessandro; Bovone, Cristina; Scorcia, Vincenzo; et al.
Abstract : Purpose: To use an automated morphometric analysis system of in vivo confocal microscopy (IVCM) images for evaluating reinnervation occurring at the subbasal nerve plexus (SNP) after direct corneal neurotization (DCN) and to further report neurophysiological and histopathological findings. Methods: Prospective interventional case series including 3 eyes with neurotrophic keratitis that underwent DCN. Deep anterior lamellar keratoplasty was performed 18 months after DCN in patient 1. The following evaluations were performed before and at 3, 6, and 12 months after DCN: clinical evolution of keratitis; corneal sensitivity; IVCM images of the SNP analyzed with "ACCMetrics;" neurophysiological study of corneal reflex. Protein gene product 9.5 immunofluorescence staining assay and transmission electron microscopy were conducted on the neurotized button excised during deep anterior lamellar keratoplasty. Results: Complete healing was obtained in all patients by 3 months postoperatively. Corneal sensitivity was absent preoperatively in all eyes and improved after surgery, reaching an average value of 30 mm 1 year postoperatively. The corneal SNP was not visible at IVCM in any of the cases preoperatively and became visible by 3 months postoperatively, showing IVCM metrics comparable to normal contralateral eyes at 1 year. In all cases, neurophysiological evaluation showed a partial recovery of the electrical activity of the cornea. In patient 1, protein gene product (PGP) 9.5 staining of neurotized cornea showed nerve fascicles at the SNP, whereas transmission electron microscopy showed amyelinic nerve axons and nerve endings. Conclusions: The corneal SNP exhibited IVCM metrics comparable to the normal contralateral eye 1 year after DCN. Ex vivo histopathological assessment of neurotized corneas confirmed the presence of nerves with normal ultrastructure.